Pengembangan Mobile Learning Berbasis Android Pada Mata Pelajaran Al-Qur’an Hadist di MTs. Al-Irsyadiyah Sarirejo Lamongan - ASYKUR MZ (Inovasi-Jurnal Diklat Keagamaan, 2021)
This study aims to developlearning media Mobile Learning an-based Android that is created using theapplication Smart Apps Creator with Qalqalah material on the Qur'anic subjects of Hadith and to know the effectiveness and appropriateness of this media which was developed and tested on 21 Grade VII students of MTs. Al-Irsyadiyah. The method used in this research is research and development (Research and Development) to produce Smartphone-based teaching material products, with the development process using the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model. But only done until the Implementation stage. Data collection techniques used a questionnaire, which was validated by material experts, media experts and teachers. The results of the validation show that the learning media of the Quran based on the android category is valid and feasible to apply, based on (1) material experts in the good category by 80 %, (2) media experts in the good category by 82 %, (3) MTs Teachers by 88 %, (4) implementation of student learning activities and assessment after learning achieved very good results. It can be stated that the application of learning based on android Qalqalah material is valid, practical and effective and feasible to be used as teaching materials of the Qur'an hadith.